In-situ EBSD observation of structure evolution in tensile deformation of NiCrMoV high-strength steel at room temperature - Guangyuan Yang; Xianglong Meng; Zhiyong Gao (Journal of Materials Research and Technology)
Studying the microstructure evolution during simple tensile loading can help understand the deformation mechanism of low carbon steel and improve the prediction accuracy of numerical simulations, exploring the path to reduce the Bauschinger effect.In this paper, the deformation mechanisms of the NiCrMoV high-strength steel during room-temperature tension were studied in detail by in-situ electron backscattered diffraction (EBSD), visco-plastic self-consistent (VPSC) modeling and slip trace analysis. It is shown that <110>//RD tension texture is formed gradually during the stretching process, while several low-angle grain boundaries (LAGBs) are formed inside the grains. Notably, the results of slip trace analysis shows that the {123}<111> slips dominate the deformation at a low strain, and with increasing strains {110}<111> slips gradually increase. The low geometrical compatibility factor between adjacent grains provide space for the accumulation of dislocations, resulting in additional hardening. The research on the deformation mechanisms of the NiCrMoV high-strength steel can help gain work hardening parameters applicable to this material, providing theoretical guidance for predicting the forming of parts with complex shapes.